READING STRATEGIES IN ISLAMIC BOARDING SCHOOL: A SMALL SCALE SURVEY - Arroza Sindiyasti (IAIN Syekh Nurjati Cirebon, 2019)
Reading strategies issues appear in EFL context, not only in formal education but also in informal education, for example in Islamic boarding school. The aims of this study is to identify the use of reading strategies by the students of Islamic boarding school. This study included 71 students at Islamic boarding school from higher education with the different studies in their university as respondents. The researcher used quantitative research with Survey of Reading Strategies (SORS) based on Mokhtari and Sheorey’s (2002) questionnaire. The questionnaire was divided into three categories: Global strategies, Problem-solving strategies, and Support strategies. There are 30 items used point Likert scale from level 1-5 as the main instrument in data retrieval. To analyze the data, the researcher using SPSS and Microsoft Excel. The result showed that the most reading strategies used by the students is problem-solving strategies with mean score = 3,952 followed reading strategies with mean score = 3,663 and the lowest one is support strategies with mean 3,633. The score of each domain indicate in high level of use. It means almost of students believe and use reading strategies while reading academic materials.